Influence of Hyponatremia on Spinal Bone Quality and Fractures Due to Low-Energy Trauma - Katharina Jäckle (MDPI AG, 2021)
Background and Objectives: Hyponatremia is the most common electrolyte disorder in elderly and associated with increased risk of falls. Clinical studies as well as small animal experiments suggested an association between chronic hyponatremia and osteoporosis. Furthermore, it has been assumed that subtle hyponatremia may be an independent fracture risk in the elderly. Therefore, this study was designed to evaluate the possible influence of chronic hyponatremia on osteoporosis and low-energy fractures of the spine. Materials and Methods: 144 patients with a vertebral body fracture (mean age: 69.15 ± 16.08; 73 females and 71 males) due to low-energy trauma were treated in a level one trauma center within one year and were included in the study. Chronic hyponatremia was defined as serum sodium < 135 mmol/L at admission. Bone mineral density (BMD) of the spine was measured using quantitative computed tomography in each patient. Results: Overall, 19.44% (n = 28) of patients in the low-energy trauma group had hyponatremia. In the group with fractures caused by low-energy trauma, the proportion of hyponatremia of patients older than 65 years was significantly increased as compared to younger patients (p** = 0.0016). Furthermore, there was no significant gender difference in the hyponatremia group. Of 28 patients with chronic hyponatremia, all patients had decreased bone quality. Four patients showed osteopenia and the other 24 patients even showed osteoporosis. In the low-energy trauma group, the BMD correlated significantly with serum sodium (r = 0.396; p*** < 0.001). Conclusions: The results suggest that chronic hyponatremia affects bone quality. Patients with chronic hyponatremia have an increased prevalence of fractures after low-energy trauma due to a decreased bone quality. Therefore, physicians from different specialties should focus on the treatment of chronic hyponatremia to reduce the fracture rate after low-energy trauma, particularly with elderly patients.